Plymorphism of walleye pollock gadus chalcogrammus mitochondrial DNA control region in the asiatic part of the range and its phylogeographic history - Orlova, Svetlana Yu; Sergeev, A. A.; Shcepetov, D. M.; Kurnosov, D. S.; Chikurova, E. A.; Orlov, Alexei M. 1960-; Glubokovsky, M. K. (Journal of ichthyology)
The phylogeographic analysis of Gadus chalcogrammus from the Asian part of the range (the western part of the Bering Sea, the Sea of Okhotsk and the Sea of Japan, the Pacific waters of the Kuril Islands and Kamchatka) based on data on the polymorphism of the mtDNA control region fragment (D-loop, 526 bp) was performed for the first time using large-scale material (1162 individuals from 38 samples). The obtained results indicate the existence of two large groups in the surveyed water area: one is localized in the western part of the Bering Sea, and the other is formed by samples from the Sea of Japan and the Sea of Okhotsk and from the Pacific waters of the Kuril Islands and Kamchatka. An unusually low level of polymorphism in the mtDNA control region of Gadus chalcogrammus was revealed, which was also previously found in G. macrocephalus and is probably due to similar microevolutionary processes that took place in the past in both species.